Effects of epilepsy on autonomic nervous system and respiratory function tests - Berilgen, MS; Sari, T; Bulut, S; Mungen, B (Academic Press Inc Elsevier Science, 2004)
We have investigated autonomic nervous system function during the interictal period in epileptic patients and the possible effects of autonomic dysfunction on respiratory functions. A total of 32 epileptic patients (23 generalized, 9 partial epilepsy) and 32 healthy volunteers were involved. Sympathetic skin response (SSR), for evaluating the sympathetic nervous system, and RR interval variation (RRIV) were measured at the beginning and third month of antiepileptic treatment, and respiratory function tests (RFTs) were performed. In patients with partial epilepsy, SSR latency in the upper extremity (1.3 +/- 0.2 s) was longer than that of controls (1.2 +/- 0.3 s) at baseline (P = 0.05), and was significantly reduced (1.1 +/- 0.3 s) after treatment (P < 0.05). RRIV values of patients with generalized epilepsy were statistically significantly lower than those of controls (P < 0.01). However, deep breathing RRIV values (32.6 +/- 15.3%) of patients were lower than those (43.0 +/- 18.2%) of controls (P < 0.05). Sympathetic dysfunction was determined in patients with partial epilepsy and parasympathetic dysfunction in patients with generalized epilepsy. No abnormality was observed on RFTs for both patients with partial epilepsy and patients with generalized epilepsy. (C) 2004 Elsevier Inc. All rights reserved.
25th International Epilepsy Congress -- OCT 12-16, 2003 -- LISBON, PORTUGAL
Keywords: epilepsy; sympathetic skin response; RR interval variation; respiratory functional tests; autonomic nervous system